2020
DOI: 10.34067/kid.0001882020
|View full text |Cite
|
Sign up to set email alerts
|

The Nephrology Immersion Classroom for Internal Medicine Residents

Abstract: BackgroundIn graduate medical education (GME), there are many barriers to achieving a personalized learning process with standardized learning outcomes. One way to support this is through mobile-friendly digital blackboard videos. We sought to measure the effect of a mobile-friendly video curriculum on resident satisfaction, knowledge, and clinical skills during a nephrology rotation.MethodsThis was a prospective, controlled, nonrandomized trial. The control group consisted of internal medicine residents who c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…However, our results are similar to other studies, which found slight increases in objective scores for certain topics delivered using the FC format 10 . Yet the data is mixed, and some studies were unable to detect a difference in scores with either format 11–13 . Furthermore, some of the literature suggests that active learning, rather than the mode of delivery of didactics curriculum, results in improved test scores 11,14 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, our results are similar to other studies, which found slight increases in objective scores for certain topics delivered using the FC format 10 . Yet the data is mixed, and some studies were unable to detect a difference in scores with either format 11–13 . Furthermore, some of the literature suggests that active learning, rather than the mode of delivery of didactics curriculum, results in improved test scores 11,14 .…”
Section: Discussionsupporting
confidence: 83%
“…10 Yet the data is mixed, and some studies were unable to detect a difference in scores with either format. [11][12][13] Furthermore, some of the literature suggests that active learning, rather than the mode of delivery of didactics curriculum, results in improved test scores. 11,14 Despite these limitations, our mode of FC delivery is unique in that it also incorporates the utilization of open-source resources, with the goal of maximizing resident efficiency in learning.…”
Section: Discussionmentioning
confidence: 99%